A Machine‐Learning Approach to Identify a Prognostic Cytokine Signature That Is Associated With Nivolumab Clearance in Patients With Advanced Melanoma. Issue 4 (19th December 2019) - Wang, Rui; Shao, Xiao; Zheng, Junying; Saci, Abdel; Qian, Xiaozhong; Pak, Irene; Roy, Amit; Bello, Akintunde; Rizzo, Jasmine I.; Hosein, Fareeda; Moss, Rebecca A.; Wind‐Rotolo, Megan; et al.
Abstract : Lower clearance of immune checkpoint inhibitors is a predictor of improved overall survival (OS) in patients with advanced cancer. We investigated a novel approach using machine learning to identify a baseline composite cytokine signature via clearance, which, in turn, could be associated with OS in advanced melanoma. Peripheral nivolumab clearance and cytokine data from patients treated with nivolumab in two phase III studies ( n = 468 (pooled)) and another phase III study ( n = 158) were used for machine‐learning model development and validation, respectively. Random forest (Boruta) algorithm was used for feature selection and classification of nivolumab clearance. The 16 top‐ranking baseline inflammatory cytokines reflecting immune‐cell modulation were selected as a composite signature to predict nivolumab clearance (area under the curve (AUC) = 0.75; accuracy = 0.7). Predicted clearance (high vs. low) via the cytokine signature was significantly associated with OS across all three studies ( P < 0.01), regardless of treatment (nivolumab vs. chemotherapy).